SPIRITUAL MEASURINGS OF EUGEN MALANYUK: HARMONY OF TROUBLE - Salyga, T. Yu. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
It is the attempt of interpretation E. Malanyuk as a literary critic and critic, essayist and publicist, culturologist and policy. An author tries to understand the aesthetically beautiful flesh of «supervisions» of Boyan Steppe Elide, conception of ideological-spiritual that ethnopsychology to the phenomenon. E. Malanyuk in scientific-critical hermeneutic of author gets up the creator of state System, Prince of Spirit, singer of Ukraine on presently pure and future times.